2017
DOI: 10.1016/j.physio.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Do isometric pull-down exercises increase the acromio-humeral distance?

Abstract: Isometric pull-down exercises lead to an increase in the acromio-humeral distance in asymptomatic males that may be clinically important, and therefore may be an appropriate exercise for patients with shoulder pathology. Ultrasound measurement of the acromio-humeral distance in 90° shoulder flexion is practical and reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…17,19,35,42 According to their findings, SRE at different shoulder abduction positions, isometric pulldown exercise, and GRE increased AHD. 17,19,35,42 To add to previous findings, our main contribution is that applying those exercises over the long term could increase the AHD in patients with SPS. Since the GRE was the only difference between groups in exercise selection, the additional effect of these exercises may have improved AHD values in our study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…17,19,35,42 According to their findings, SRE at different shoulder abduction positions, isometric pulldown exercise, and GRE increased AHD. 17,19,35,42 To add to previous findings, our main contribution is that applying those exercises over the long term could increase the AHD in patients with SPS. Since the GRE was the only difference between groups in exercise selection, the additional effect of these exercises may have improved AHD values in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have demonstrated the initial effect of exercises on AHD. 17,19,35,42 According to their findings, SRE at different shoulder abduction positions, isometric pulldown exercise, and GRE increased AHD. 17,19,35,42 To add to previous findings, our main contribution is that applying those exercises over the long term could increase the AHD in patients with SPS.…”
Section: Discussionmentioning
confidence: 97%
“…30 Additionally, there is only very limited evidence that humeral head procedures actually influence humeral head position. 31 The SSMP assessment form is detailed in figure 1. The specific assessment procedures have been described elsewhere.…”
Section: Introductionmentioning
confidence: 99%